Ludwig's Angina: A comprehensive analysis of diagnosis, treatment options, and their clinical correlations (Research, Society and Development, 2023)
Ludwig's Angina is a serious infectious condition that affects the facial and oral spaces of the stomatognathic system, presenting distinctive symptoms, such as stiffening of the floor of the mouth, dysphagia, dyslalia and risk of airway obstruction. Treatment of this pathological entity includes early diagnosis and maintenance of patent airways. The objective of the present work is to provide a comprehensive analysis that addresses the history, diagnosis, treatment and clinical implications of this disease, highlighting the importance of early diagnosis and appropriate treatment. The search was carried out through the National Library of Medicine (PUBMED) databases on September 26, 2023 and Scientific Electronic Library Online (SCIELO) on September 1, 2023, with the MeSH descriptors: “Ludwig's angina'', “Infections '' and ''Infectious Dermatopathies'' combined using the Boolean operator "AND", without limitations on language, publication date, gender or age of participants. During the search, 450 articles were found, resulting from 309 in SCIELO and 141 in PUBMED. Of these, 300 articles were initially read (reading the titles and abstracts) and, after exclusion criteria that included articles published after 1990, non-original articles, duplicates, errata, comments, letters and articles not made freely available in full, 36 articles remained selected. for complete reading, all meeting the inclusion criteria. The comprehensive analysis based on rigorous literature review provides essential information for the effective management of this condition, aiming to improve patients' quality of life and prevent serious complications.